Abnormal thymic stromal lymphopoietin expression in the gastrointestinal mucosa of patients with eosinophilic gastroenteritis - Hongmei Guo; Xiaolan Ji; Guang Yang; Yu Jin (Brazilian Society of Pediatrics, 2020)
Objective: To investigate the differential expression of the thymic stromal lymphopoietin isoforms, short and long, and discern their biological implications under eosinophilic gastroenteritis. Methods: The expression of thymic stromal lymphopoietin and its two isoforms in tissues was assessed by quantitative RT‐PCR in healthy controls (n = 24) and patients with eosinophilic gastroenteritis (n = 17). Results: Thymic stromal lymphopoietin mRNA was significantly reduced in eosinophilic gastroenteritis when compared with healthy controls (p < 0.0001). A significantly lower amount of short thymic stromal lymphopoietin mRNA was observed in eosinophilic gastroenteritis when compared with controls (p < 0.05), while a significantly higher amount of long thymic stromal lymphopoietin mRNA was observed in eosinophilic gastroenteritis when compared with controls (p < 0.05). Peak eosinophilic count is significantly positively correlated with the expression of long thymic stromal lymphopoietin mRNA in the gastrointestinal mucosal of patients with eosinophilic gastroenteritis (rs = 0.623,p < 0.005), while peak eosinophilic count is significantly negatively correlated with the expression of short thymic stromal lymphopoietin mRNA in the gastrointestinal mucosal of patients with eosinophilic gastroenteritis (rs = ‐0.4474, p < 0.05). Conclusions: Abnormal mucosal thymic stromal lymphopoietin expression may contribute to gastrointestinal mucosa damage in eosinophilic gastroenteritis. Resumo: Objetivo: Investigar a expressão diferencial das isoformas da linfopoietina estromal tímica, curta e longa, e discernir suas implicações biológicas na gastroenterite eosinofílica. Métodos: Avaliamos a expressão das isoformas da linfopoietina estromal tímica e suas duas isoformas através da técnica RT‐PCR quantitativa em tecidos de controles saudáveis (n = 24) e pacientes com gastroenterite eosinofílica (n = 17). Resultados: Demonstramos que o RNAm das isoformas da linfopoietina estromal tímica estava significativamente reduzido na gastroenterite eosinofílica em comparação com os controles saudáveis (p < 0,0001). Também descobrimos uma quantidade significativamente menor de RNAm das isoformas da linfopoietina estromal tímica curta na gastroenterite eosinofílica em comparação com os controles (p < 0,05) e uma quantidade significativamente maior de RNAm das isoformas da linfopoietina estromal tímica longa na gastroenterite eosinofílica em comparação com os controles (p < 0,05). O pico da contagem eosinofílica está correlacionado positiva e significativamente com a expressão do RNAm das isoformas da linfopoietina estromal tímica longa na mucosa gastrointestinal de pacientes com gastroenterite eosinofílica (rs = 0,623, p < 0,005), enquanto o pico de contagem eosinofílica está negativa e significativamente correlacionado com a expressão do RNAm das isoformas da linfopoietina estromal tímica curta na mucosa gastrointestinal de pacientes com gastroenterite eosinofílica (rs = ‐0,4474, p < 0,05). Conclusões: A expressão anormal das isoformas da linfopoietina estromal tímica na mucosa pode contribuir para o dano da mucosa gastrointestinal na gastroenterite eosinofílica.